Exploring The Empowering Influence of Prof. K.G Parashuram’s Dynamic Personality on Advancing Social Work Initiatives - Bhavya. P (PT FORMOSA CENDEKIA GLOBAL, 2024)
The study, which explores the empowering influence of Prof. K.G Parashurama's dynamic personality on advancing social work initiatives. Through qualitative analysis and case studies, the research uncovers how Prof. Parashurama's motivational approach catalyzes positive change within the social work landscape. It reveals a significant correlation between Prof. Parashurama's dynamic leadership style and the advancement of various social projects, emphasizing the importance of inspirational figures in driving impact societal change. The implications extend to leadership development within the social work sector, offering insights into fostering a more vibrant and effective community welfare framework